ANALISIS DIMENSI PROSES KOGNITIF KATEGORI (C4) SISWA SMP KELAS IX TENTANG MATERI LISTRIK - Rahmawati; Darsikin; Pasaribu, Marungkil (Universitas Tadulako, 2021)
This study aims to describe the dimensions of the cognitive process category (C4) about the Electrical material in students. This research is a descriptive-qualitative type of research. The research subjects amounted to 31 students who were then given a test in the form of an essay to determine the respondents as many as 6 people. The data was obtained from the cognitive process dimension test category (C4) about electrical material with thinking-aloud settings. From the results of the research conducted, the results show that the achievement of the cognitive process dimension analysis of students at the level (C4) can be classified as low category, namely 51.09%. Overall, the percentage of the results of the analysis of the dimensions of cognitive processes in the C4 category in class IX students, namely the combined descriptor obtained a value of 66.67%, the descriptor combined coherence of 55%, the descriptor made an outline of 55%, the descriptor chose 50.83%, and deconstructing descriptor is 79.16%.